Pemanfaatan α-Tokoferol untuk Meningkatkan Profil Superoksida Dismutase (SOD) Ginjal Tikus di Bawah Kondisi Stres - Tutik Wresdiyati; Made Astawan; Diini Fithriani; I Ketut Mudite Adnyane; Mustika Hidayati (Universitas Atma Jaya Yogyakarta, 2008)
Stress condition has been reported decreased the level of intracellular antioxidant, especially superoxide dismutase (SOD). The condition can lead to certain cell impairment and finally can reach to the degenerative processes, such as aging and carcinogenesis. We need several alternative treatments to solve the severe problem under antioxidant defiency status caused by stress condition. The aim of the study was to observe the effect of α-tocopherol on increasing the profile of superoxide dismutase (SOD) in the kidney of rats under stress condition. The stress condition was achieved by five days fasting together with smimming for 5 min/day and only drinking distiled water ad libitum. α-tocopherol was orally administrated at a dose of 60 mg/Kg/BW/day for seven days. By measuring SOD activity and Cu,Zn-SOD imunohistochemically, showed that α-tocopherol has effect on increasing the profile of intracellular antioxidant in the rats kidney tissue under stress condition.